SHARPENING TEETH IN THE HOSPITAL FOR THE PREPARATION OF COATING (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
In this article, we examined the methods of sharpening a tooth in a hospital for coating grinding